Friction and wear behavior of annealed Ti-20Zr-6.5Al-4V alloy sliding against 440C steel in vacuum. (May 2017) - Zhong, H.; Dai, L.Y.; Yue, Y.; Zhang, B.; Feng, Z.H.; Zhang, X.Y.; Ma, M.Z.; Khosla, T.; Xiao, J.; Liu, R.P.
Abstract: Tribological behavior of a recently-developed Ti-20Zr-6.5Al-4V alloy was tested in vacuum at different annealing temperatures (800 °C, 900 °C and 1000 °C). Coefficient of friction and wear volume of the Ti-20Zr-6.5Al-4V alloy in vacuum were obtained. Scanning electron microscopy analysis was employed to determine the wear mechanism. Results show that the main wear mechanism changes from mild adhesive and severe abrasive wear at 10 N loading to severe plastic deformation and delamination wear at 30 N loading. A transfer layer was found on the stainless steel ball surface and the EDS results reveal that the layer originates from the Ti-20Zr-6.5Al-4V alloy. The three dimensional topography of the Ti-20Zr-6.5Al-4V worn surface was also explored. Highlights: Tribological tests of a recently-developed Ti-20Zr-6.5Al-4V alloy are conducted in vacuum. COF of TiZrAlV disc sliding against 440C steel ball in vacuum is in the range from 0.34 to 0.43. Wear mechanisms of the TiZrAlV alloy are varied with the normal load and annealed temperatures. 3D topologies show that the wear scars become fewer, deeper and wider with increasing the load.